Toxoplasma gondii from liquid nitrogen for continuous cell culture: methods to maximize efficient retrieval...reprinted from British Journal of Biomedical Science 2003 60(4) with permission of the publisher - Mavin S; Evans R; Chatterton JMW; Ashburn D; Joss AWL; Ho-Yen DO (Journal of Continuing Education Topics & Issues, 2005)
This study aims to increase the efficiency of continuous growth of Toxoplasma gondii in HeLa cells from tachyzoite stocks frozen in liquid nitrogen. Freezing and retrieval of tachyzoites for continuous cell culture requires more stringent protocols than those published for animal culture. The freezing and retrieval conditions are optimized so that a quality harvest (>/=1 x 10[6] tachy-zoites/mL, >/= 90% viability) can be produced using T. gondii recovered from liquid nitrogen as fast and reliably as possible. Retrieval success rate in-creased from 36% to 100%. An improved freezing procedure using chilled reagents and freshly harvested parasites, and adoption of an effective recovery protocol with retrieval of 3 x 10[7] tachyzoites into 75cm[2] flasks, change of maintenance media after six hours and subsequent blind passage all contributed to this success. The result is faster and more dependable production of T gondii for diagnostic and experimental use.